Measuring Equity in Iranian Healthcare System Financing: Experiences of Recent Health Reform Plan - Abdolvahed Khodamoradi; Shahram Ghaffari; Amir Abbas Fazaeli; Reza Toyserkanmanesh; Vahid Rasi; Fariba Bigdeli (Shahid Sadoughi University of Medical Sciences, 2019)
Background: One of the main goals of the health system is the fair contribution of people to healthcare financing. Therefore, the current study not only evaluated the status of fair financial contribution, but also investigated the impacts of the health reform plan on the financial pillars of the Iranian healthcare system. Methods: To conduct this retrospective descriptive study, the data of Income and Expenditure Survey (2011-2015) commissioned by Statistical Center of Iran were used. To measure fairness of financing, four indices were used. Data were analyzed using the Excel and SPSS software. Results: The results show that although the health reform plan has increased insurance coverage of both rural and urban households, out of pocket, and even its proportion to household capacity to pay continues to rise. Prevalence of catastrophic health expenditures in the baseline year in rural and urban areas was 2.19% and 1.04%, reaching 3.69% and 2.39% at the end of the study, respectively. Accordingly, fair financial contribution in rural and urban areas was obtained 0.830% and 0.850% in the baseline year, reaching 0.823% and 0.850% in the last year of the study, respectively. Conclusion: Although indices of fair financial contribution during the 5-year period varied, they ultimately showed a worse situation compared to the baseline year. Thus, it is assumed that the health reform plan has not yet been successful in meeting the goal of improving fair financial contribution to the health system.